Cover Picture: Structure–Activity Relationships of Glycogen Phosphorylase Inhibitor FR258900 and Its Analogues: A Combined Synthetic, Enzyme Kinetics, and Computational Study (ChemPlusChem 11/2014). Issue 11 (November 2014) - Juhász, László; Varga, Gergely; Sztankovics, Andrea; Béke, Ferenc; Docsa, Tibor; Kiss‐Szikszai, Attila; Gergely, Pál; Kóňa, Juraj; Tvaroška, Igor; Somsák, László
<x xml:space="preserve">Abstract</x> The front cover picture shows the structure of the natural product FR258900, an inhibitor of glycogen phosphorylase (GP), which served as the lead compound for several series of synthetic analogues. Binding mode of the best inhibitor in the allosteric site of GP as revealed by molecular docking was also illustrated. It was shown by synthesis, enzyme kinetics, and computational methods that inhibitory compounds have two acyl side chains and tartaric acid can replace the pentanedioic acid core of the lead. Details of these studies including a quantitative structure–activity relationship suitable for further design of inhibitors are described in the Full Paper by L. Somsák et al. on page 1558.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>